2021
DOI: 10.46627/silet.v2i3.88
|View full text |Cite
|
Sign up to set email alerts
|

Burnout Syndrome During the Covid-19 Pandemic among Visual Art Teachers in Ghana

Abstract: This study sought to address burnout syndrome during the COVID-19 global pandemic among visual art teachers in Ghana. The startling intricacies of COVID-19 burnout among Visual Art Teachers (VAT) in Ghana were discovered using an exploratory research approach. 112 participants were surveyed across Senior High Schools Visual Art Teachers in Ghana. Data were analyzed using t-test, regression, and analysis of variance test (F test) to determine whether there were significant differences between the burnout levels… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 35 publications
0
1
0
Order By: Relevance
“…Although we expected some significant correlations between age, number of students and burnout and perceived stress, our data did not highlight the expected results. However, we were not that surprised given the fact that there are other studies that have shown contrasting results regarding the association between age and burnout or stress (Osei et al, 2021;Sánchez-Pujalte et al, 2021).…”
Section: Discussionmentioning
confidence: 53%
“…Although we expected some significant correlations between age, number of students and burnout and perceived stress, our data did not highlight the expected results. However, we were not that surprised given the fact that there are other studies that have shown contrasting results regarding the association between age and burnout or stress (Osei et al, 2021;Sánchez-Pujalte et al, 2021).…”
Section: Discussionmentioning
confidence: 53%
“…Future research would need to establish which factors are responsible for job engagement and employee well-being in order to explore possible burnout intervention and prevention strategies (Akhrem & Gazdowska, 2016). The primary idea is that individuals have a larger role to play in preventing burnout, even in high-responsibility job roles (Osei et al, 2021). Burnout prevention strategies may be focused on organizational changes or individual aspects (Matsuzaki et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Among the causes of psychological issues skilled with the aid of college students when studying online during the pandemic period came from teachers (Sakka et al, 2020). This is because the teacher also feels tired which has an effect on his psychology, physique, and capacity as a teacher such as less productivity, undeveloped teaching skills, irritability, and health problems (Osei et al, 2021). These conditions require the ability to survive, and adapt positively (academic resilience) because it will affect self-efficacy and achievement when learning online (Martin et al, 2021;Warshawski, 2022).…”
Section: Introductionmentioning
confidence: 99%